Direct and cross impacts of upwind emission control on downwind PM2.5 under various NH3 conditions in Northeast Asia - Kim, Eunhye; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Environmental Pollution, 2021)
Emissions reductions in upwind areas can influence the PM2.5 concentrations in downwind areas via long-range transport. However, few studies have assessed the impact of upwind PM2.5 precursor controls on changes in downwind PM2.5 concentrations. In this study, we analyzed the overall impact of PM2.5 precursor emission controls in upwind areas on PM2.5 in downwind areas with two types of impacts: “direct impact” and “cross impact.” The former refers to PM2.5 changes in downwind areas due to the transported PM2.5 itself, whereas the latter represents PM2.5 changes due to reactions between the transported gaseous precursors and intermediates (i.e., HNO3) originating from upwind areas and locally emitted precursors (i.e. NH3) in the downwind areas. As a case study, we performed air quality modeling for Northeast Asia for January 15–17, 2016 by setting China and South Korea as the upwind and downwind areas, respectively. To account for potential spatiotemporal variations in NH3 emissions in downwind areas, we considered two NH3 conditions. When NOx emissions in China were reduced by 35%, in downwind areas the PM2.5 concentrations decreased by 2.2 μg/m3 under NH3-rich conditions, while PM2.5 concentrations increased by 2.3 μg/m3 under NH3-poor conditions. The direct impact increased by 4.0 μg/m3 in both cases due to upwind NOx disbenefit effects. However, the cross impacts led to a PM2.5 decrease of 6.2 μg/m3 under NH3-rich conditions versus a PM2.5 increase of 1.7 μg/m3 under NH3-poor conditions. We noted that PM2.5 concentrations in the downwind areas may not improve unless a cross impact outweighs a direct impact. This may be one of the reasons why South Korea PM2.5 concentrations have not declined despite efforts by China to reduce their PM2.5 precursor emissions.
Keywords: Air quality modeling; Emissions reduction; Gaseous precursors; Long range transport; Northeast Asia; PM2.5 concentration; Rich conditions; Spatio-temporal variation; Air Pollutants; Air Pollution; Asia; China; Environmental Monitoring; Particulate Matter; Republic of Korea; Vehicle Emissions; Downwind; Emissions control; Long-range transport; Particulate matter; Upwind